2004
DOI: 10.1007/s11748-004-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative trans-mitral endoscopic resection of left ventricular tumor

Abstract: A successful resection of left ventricular tumor in an 82-year-old woman who had undergone coronary artery bypass grafting ten years ago is presented. In an attempt to make a procedure less invasive, we chose a trans-mitral endoscopic resection with minimum dissection because of reoperation on patient of advanced age. With the use of cardiopulmonary bypass and cardioplegic protection, the right side of left atrium was incised longitudinally. The endoscope was inserted in the ventricle via the mitral valve. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This was followed by semi-rigid endoscopes in four [7, 9, 21, 29], flexible endoscopes in three [2, 3, 30] and mixture of rigid and flexible endoscopes in one study [11]. In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was followed by semi-rigid endoscopes in four [7, 9, 21, 29], flexible endoscopes in three [2, 3, 30] and mixture of rigid and flexible endoscopes in one study [11]. In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35]. Other adjunct endoscopic instruments such as forceps, graspers, scissors, suckers or retractors were used in 13 studies [2, 3, 12, 13, 15, 19, 21, 25, 30, 32, 34, 35, 37]. In the remaining it was not clear whether open surgical or endoscopic instruments were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kudo et al reported an intraoperative transmitral endoscopic resection of a left ventricular tumor. 3 Misumi et al reported two cases of endoscopic resection of left ventricular tumors through the mitral valve and the aortic valve. 4 Li et al reported a technique using video-assisted cardioscopy to remove a left ventricular myxoma.…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported the first case of an endoscopic transmitral resection of a left ventricular papillary fibroelastoma. 1 In this paper, we describe this technique in detail. revealed all bypass grafts to be patent.…”
Section: Introductionmentioning
confidence: 99%